Formation of preparedness for professional activity by ICT means - Senkivska, L. (Journal of Education, Health and Sport, 2021)
The article considers the current state of the problem of forming the readiness of future professionals for professional activities by ICT. The author proved that the training of future specialists in pedagogical specialties in the application of ICT requires a slightly different view of this complex creative process, which requires constant dynamic updating and application of the most effective and diverse methods of higher education.